2022
DOI: 10.3390/molecules27030877
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties and Composition of Binary Kolliphor Mixtures at the Water–Air Interface at Different Temperatures

Abstract: The studies on the adsorption properties and composition of the adsorbed monolayer at the water–air interface of the binary Kolliphor® ELP (ELP) and Kolliphor® RH 40 (RH40) mixtures based on the measurements of the surface tension (γLV) of their aqueous solution in the temperature range from 293 to 318 K were carried out. The γLV isotherms were described by the exponential function of the second order and the Szyszkowski equation as well as predicted by Fainerman and Miller equation. The obtained γLV isotherms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…It seems, however, that despite the strong interactions between the TX165 molecules and those of biosurfactants, the mole fraction of the mixture components in the mixed monolayer at the water–air interface does not differ much from that calculated based on the monolayer pressure of individual compounds. This conclusion confirms the surface tension isotherms of the aqueous solution of TX165 mixtures with the biosurfactants determined from the following expression [ 33 ]: …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It seems, however, that despite the strong interactions between the TX165 molecules and those of biosurfactants, the mole fraction of the mixture components in the mixed monolayer at the water–air interface does not differ much from that calculated based on the monolayer pressure of individual compounds. This conclusion confirms the surface tension isotherms of the aqueous solution of TX165 mixtures with the biosurfactants determined from the following expression [ 33 ]: …”
Section: Resultssupporting
confidence: 86%
“…It seems reasonable to assume that the of the TX165 mixtures with RL or SF is equal to where is the mole fraction of the particular surfactants in the mixture and 1, 2, and 12 refer to TX165, the biosurfactant, and the mixture of TX165 with the biosurfactant, respectively. As was stated earlier [ 33 ], and ( and are the layers surfactants 1 and 2 pressure, respectively). Taking into account the values determined in this way, the values for the TX165 + RL and TX165 + SF mixtures at a given concentration and composition were deduced.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The determination of the surface tension components and parameters of ELP and RH40 is not easy. It was found that the minimal surface tension of the aqueous solution of surfactants satisfies the condition [ 10 ]: where X S and X W are the fraction of the interface area occupied by the surfactant and water, and γ S and γ W are the surface tension of the surfactant tail and water.…”
Section: Resultsmentioning
confidence: 99%
“…The large hydrophobic tail of the ELP and RH40 molecules includes three hydrocarbon chains with one –OH group in each chain. The hydrophilic head of these surfactants includes oxyethylene groups [ 10 , 11 ]. Due to the large contact area of the hydrophobic parts of ELP and RH40 molecules, it is possible that strong interactions can occur between these parts and the AuO molecules, resulting in the great effect of AuO on the adsorption and aggregation of ELP and RH40 as well as their mixtures.…”
Section: Introductionmentioning
confidence: 99%